If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19 = 11 + -6X Solving -19 = 11 + -6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6X' to each side of the equation. -19 + 6X = 11 + -6X + 6X Combine like terms: -6X + 6X = 0 -19 + 6X = 11 + 0 -19 + 6X = 11 Add '19' to each side of the equation. -19 + 19 + 6X = 11 + 19 Combine like terms: -19 + 19 = 0 0 + 6X = 11 + 19 6X = 11 + 19 Combine like terms: 11 + 19 = 30 6X = 30 Divide each side by '6'. X = 5 Simplifying X = 5
| (4x-2)4x-2+5x(5x)= | | -5y-7(9y+7)=1+3(-7-y) | | y-9(5)=3 | | 4x^2+0.2x+0.01=0 | | 4(u+1)-7=3(u-1)+7 | | -x+3.9forx=-7.2 | | (4x+2)=-34 | | 9+4(-4)+3=-4 | | (4x+2)=34 | | 0.80x+0.20(60)=0.40(78) | | -3.6-7.2=12.7-6.1b | | (4x-2)(4x-2)+(5x)(5x)= | | 10x-4-6x=5x-7 | | (-10)+4=-2(-10)+-6 | | 2a+8=4a+16 | | 5(4x-4)-9=-31 | | 216=8(-5r-3) | | (3x+y*1)=(7*2x-3y) | | 29.95=42-sqrt(0.001x+2) | | (x^2+2xy)dx+xdy=0 | | 5w-6=60 | | 18=9x+4-2x | | (3+2x)=0.5x+1 | | 7x+10=4x-16 | | 3X=6-3 | | -19=v/10 | | 3x+3x-7=47 | | 2x[2+(5+2)]= | | ln(9x)=2ln(2x) | | 5(4x-4)-9=31 | | X-4y+15=0 | | -3x+4x-10=15x+1 |